Endosomal pH modulation by peptide-gold nanoparticle hybrids enables potent anti-inflammatory activity in phagocytic immune cells. (December 2016) - Yang, Hong; Kozicky, Lisa; Saferali, Aabida; Fung, Shan-Yu; Afacan, Nicole; Cai, Bing; Falsafi, Reza; Gill, Erin; Liu, Mingyao; Kollmann, Tobias R.; Hancock, R.E.W.; Sly, Laura M.; et al.
Abstract: Toll-like receptor (TLR) signaling plays a central role in the pathophysiology of many acute and chronic human inflammatory diseases, and pharmacological regulation of TLR responses is anticipated to be beneficial in many inflammatory conditions. Currently there are no specific TLR inhibitors in clinical use. To overcome this challenge, we have developed a nano-based TLR inhibitor (peptide-gold nanoparticle hybrids) that inhibits a broad spectrum of TLR responses. Through mechanistic studies, we established that specific peptide decorated-gold nanoparticles that display high cellular uptake in phagocytic immune cells modulate endosomal pH, leading to significant attenuation of signaling through multiple TLRs. Using a global transcriptomic approach, we defined the broad anti-inflammatory activity of the nanoparticle in human peripheral blood mononuclear cells. In vivo studies confirmed the beneficial immunomodulatory activity since treatment with the nanoparticle significantly reduced weight loss, improved the disease activity index, and ameliorated colonic inflammation in a murine model of intestinal inflammation. This work enhances our fundamental understanding of the role of peptide coatings on the nanoparticle surface in regulating innate immune signaling, and identifies specific peptide decorated nanoparticles that may represent a novel class of anti-inflammatory therapeutics for human inflammatory diseases. Graphical abstract: